The Use of Augmented Reality in the Teaching and Learning of isiXhosa Poetry (Journal of the Digital Humanities Association of Southern Africa, 2024)
Teaching and learning isiXhosa poetry continues to pose challenges for both teachers and learners in South African basic education. The abstract nature of poetry makes it difficult for both groups to grasp the figurative meanings embedded in each line of the poems. Teachers who rely on rote learning and learners who master cramming find teaching and learning poetry difficult, as these skills offer little or no results in the teaching and learning of poetry. It is against such a backdrop that this paper seeks to investigate the use of augmented reality (AR) in education and how it can assist in the teaching and learning of isiXhosa poetry. The use of AR in language learning has been extensively studied by several scholars. AR is found to enhance learning and decrease learners’ cognitive load. In contrast, some scholars argue that it is not ready for total integration into language classes. Despite strides that have been made in the study of augmented reality in language learning and teaching, there is a paucity of extended research on the use of augmented reality in teaching and learning isiXhosa poetry. In this paper, I will review existing data and examine augmented reality activities and technologies that can be used in the teaching and learning of IsiXhosa poetry. This paper will contribute towards improving the teaching and learning of isiXhosa poetry in basic education and assist literature educators in integrating modern technologies in their teaching.
Keywords: Augmented Reality; isiXhosa poetry; Teaching and Learning; AR technologies; AR activities